22=2(y-7)-6y

Simple and best practice solution for 22=2(y-7)-6y equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 22=2(y-7)-6y equation:



22=2(y-7)-6y
We move all terms to the left:
22-(2(y-7)-6y)=0
We calculate terms in parentheses: -(2(y-7)-6y), so:
2(y-7)-6y
We add all the numbers together, and all the variables
-6y+2(y-7)
We multiply parentheses
-6y+2y-14
We add all the numbers together, and all the variables
-4y-14
Back to the equation:
-(-4y-14)
We get rid of parentheses
4y+14+22=0
We add all the numbers together, and all the variables
4y+36=0
We move all terms containing y to the left, all other terms to the right
4y=-36
y=-36/4
y=-9

See similar equations:

| u+12=82 | | w+34=80 | | -7(-3u+3)-4u=3(u-8)-5 | | (12y-6)/6=2y-1 | | 6(u-6)=8u-38 | | d−–130=791 | | q-149=2 | | 3(w+5)-5w=19 | | d-67=4 | | 2(4x+7)=6/ | | g-8=63 | | -5(u+1)=u-2+3(2u+5) | | 13=z+8 | | -14/2=2x/2 | | s-13=7 | | 5u+26=8(u+7) | | |x+2|=-11 | | x*x=1,600 | | 6=2(x-5)-4x | | 10(2x-150)=600 | | 6/p+9=14 | | 4y+4-2(-8y-1)=6(y-2) | | H(x)=-2x2+1x+6 | | -6(w+4)=-8w-16 | | (2.25)/(100)=(x)/(40) | | 36=z+z+z+5+z+5 | | 9r=12r−9 | | 4=5s-6 | | -3x-6=-6x-3 | | 8/x=28 | | 2.5p–20=9p+37.5 | | 19=5s-6 |

Equations solver categories